A Case of Medullary Carcinoma of Thyroid (Anwer Khan Modern Medical College Journal, 2022)
A 50-year-old diabetic female attended in September, 2021 with a huge swelling in front of her neck, respiratory distress, hoarseness of voice, & generalized weakness for 1 month. All the biochemical tests were inconclusive but S. calcitonin was high(>0.08ng/ml), Fiber optic laryngoscopy revealed left vocal cord paralysis, X-ray chest revealed right sided tracheal deviation, CT-scan of Neck revealed large solid mass in thyroid with mediastinal extension & cervical lymphadenopathy. Patient undergone total thyroidectomy. The specimen sent for histopathology and revealed medullary carcinoma of thyroid gland.AKMMC J 2021; 12(2): 104-106